Centromere protein U (CENPU) enhances angiogenesis in triple-negative breast cancer by inhibiting ubiquitin–proteasomal degradation of COX-2. (10th July 2020) - Pan, Teng; Zhou, Dongdong; Shi, Zhendong; Qiu, Yufan; Zhou, Guanglin; Liu, Jingjing; Yang, Qianxi; Cao, Lixia; Zhang, Jin
Abstract: Triple-negative breast cancer (TNBC) is characterized by high vascularity, but anti-angiogenic therapies show poor efficacy. Centromere protein U (CENPU), a centromere component essential for mitosis, is associated with tumorigenesis in multiple cancers; however, little is known of its role in breast cancer. Here, we investigate its expression and function of promoting angiogenesis in TNBC. Immunohistochemical staining revealed high CENPU expression in TNBC tissue and high CENPU levels correlated significantly with poor distant metastasis-free and overall survival. Knockdown of CENPU in TNBC cells inhibited vascular endothelial growth factor A (VEGFA) production and significantly reduced tube formation and migration of human umbilical vein endothelial cells in vitro . In a mouse xenograft model, CENPU knockdown reduced TNBC tumor growth concomitant with a reduction in CD31 + microvessel density. Mechanistic studies revealed that CENPU promoted angiogenesis by inhibiting the ubiquitination and proteasomal degradation of cyclooxygenase-2 (COX-2), leading to increased activation of the COX-2–p-ERK–HIF-1α–VEGFA signaling pathway. Taken together, our results demonstrate a critical role for CENPU in COX-2-mediated signaling for angiogenesis, and identify a role of CENPU in regulating angiogenesis in TNBC. Highlights: CENPU is overexpressed in TNBC and predicts poor survival. CENPU knockdown in TNBC cells inhibits angiogenesis in vitro . CENPU stabilizes COX-2 protein by inhibiting its ubiquitination. CENPU knockdown inhibits TNBC angiogenesis and growth in a mouse model.